Sistem Bagi Hasil Pertanian Pada Masyarakat Petani Penggarap di Kabupaten Gorontalo Perspektif Hukum Ekonomi Islam - Rizal Darwis (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2016)
Discourse on the cooperation system of agricultural land in the Islamic jurisprudence has to be specific regulated with a familiar term: mudharabah, muzara’ah, musaqah, and mukhabarah. This paper examines the system for the agricultural community in the district of Gorontalo sharecroppers perspective of economics Islamic law. It is a descriptive qualitative research and the data was collected using observation, interviews, and document review. Finding of this study revealed that adapted form of profit sharing land with the agreement of both parties, such as one-half, one-third and one-quarter to see who the provider of seed and operational costs and see nature if crop failure. Implementation of the system for this result is in line with the legal concept of Islamic economics by eliminating injustice to the parties whom to contract it. In addition, these practices have a positive impact for smallholders to raise the level of the economy.